Analisis Dampak Transportasi Rel terhadap Penurunan Tingkat Kemacetan di Jakarta - Oce Ovalina Yumame; Sapto Pramono; Ika Devy Pramudiana (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This study aims to analyze the impact of implementing rail transportation on traffic congestion in Jakarta. The background of this research is driven by the increasing congestion, which has become a major issue in the Jakarta metropolitan area, affecting time efficiency and air quality. The objective of this research is to evaluate the effect of increased use of rail transportation, such as KRL, MRT, and LRT, in reducing congestion in Jakarta. This study uses a comparative analysis method with both quantitative and qualitative approaches, combining data on congestion levels, the growth of private vehicles, and the increase in rail transportation passengers from 2019 to 2024. The results show that although the number of private vehicles continues to rise, congestion can be significantly reduced with the increase in rail transportation users. The increased use of KRL, MRT, and LRT has contributed to the reduction of private vehicle volume on the roads, which has been proven to help reduce congestion and air pollution. The implications of this research are that the development and integration of a more extensive rail transportation system can be an effective solution in addressing congestion, improving public mobility in Jakarta, and supporting environmental sustainability.